PEYGAMBER TASAVVURUNDAKİ DEĞİŞİMİN DİLE ve EDEBİYATA YANSIMASI: NA?T-I ŞERÎF ÖRNEĞİ - (:unkn) unknown (My University, 2014)
Eski Türk edebiyâtında Hz. Peygamber'i konu alan pek çok edebî tür mevcuttur. Bunlar arasında na?tlar ilk sırada gelir. Peygamber sevgisinin konu edildiği na?tlar, Yeni Türk edebiyatı devresinde de sayıca daha az olmakla birlikte yazılmaya devam etmiştir. Ancak her iki devrede ortaya konan örnekler arasında hem adet hem içerik bakımından belirgin farklılıklar tespit edilmiştir. Bu makale, eski ve yeni na?tlar arasındaki mâhiyet değişikliğinin sebepleri üzerinde bir değerlendirme yapmayı hedeflemektedir.

Classical Turkish literature includes many literary types describing the Prophet. Naats come as first between those and have been continued to be written also at the time of New Turkish literature, although fewer in number. However, for both examples significant differences in terms of both quantity and content have been identified. This article aims to make an assessment on which reasons cause the changes of the nature between the old and new naats.
The Chancing Concept of the Prophet Which Reflects in Language and Literature: the Case of Naat
Keywords: Kültürel Çalışmalar; Folklor; Tarih; Edebiyat; Din Bilimi